Children as Robot Designers - Alves-Oliveira, P.; Arriaga, P.; Paiva, A.; Guy Hoffman (16th ACM/IEEE International Conference on Human-Robot Interaction Conference (HRI), 2021)
We present the design process of a robot aimed at stimulating creativity in children. The robot was developed under a user-centered design approach with participatory design practices during a two-year period and involving 142 children as active contributors at all design stages. The main contribution of this work is the development of methods and tools for child-centered robot design. To achieve this goal, we adapted existing participatory design practices used with adults to fit children’s development stages. We used formative design, which consists of an intermediate assessment of the robot with users in real-world contexts, to improve the robot. We followed the Double-Diamond Design Process Model and rested the design process on the following principles: low floor and wide walls, creativity provocations, open-ended playfulness, and disappointment avoidance through abstraction. The final product is a social robot designed for and with children, that has the potential to stimulate their creativity during play. We identified several guidelines that made the design process successful: the use of toys as tools, the use of playgrounds as spaces, the emphasis of playfulness for child expression, and child policies as allies for child design studies. This design process empowers children’s voices in the design of robots.